1997
DOI: 10.1159/000190244
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Calcification in Long-Term Haemodialysis Patients in a Single Unit: A Retrospective Analysis

Abstract: Vascular calcification (VC), which is described in the elderly and in diabetics, is frequently seen in uraemia. It is usually regarded as having little significance. We studied the roentgenological appearance of VC in a homogeneous group of 38 long-hours haemodialysis patients whose longevity on dialysis allowed sustained (10-25 years) follow-up, including annual skeletal surveys and thrice-yearly clinical examinations and biochemical profiles. We compiled a dossier of clinical and laboratory parameters from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
136
1
14

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(153 citation statements)
references
References 13 publications
1
136
1
14
Order By: Relevance
“…A more recent investigation conducted by Sharma et al (44) observed significantly reduced rates of all-cause and cardiovascular mortality in 150 dialysis patients who underwent near-total parathyroidectomy relative to 1044 non-PTX control patients. Accumulating evidence showed that successful PTX in severe SHPT patients led to substantial cardiovascular benefits, including improvement in BP (11,45), amelioration of uremic tumoral calcinosis (46,47), decrease in thickness of coronary artery intima media (10), and reduction in left ventricular mass index (48). However, whether successful PTX can affect cardiac autonomic outflow in severe SHPT remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent investigation conducted by Sharma et al (44) observed significantly reduced rates of all-cause and cardiovascular mortality in 150 dialysis patients who underwent near-total parathyroidectomy relative to 1044 non-PTX control patients. Accumulating evidence showed that successful PTX in severe SHPT patients led to substantial cardiovascular benefits, including improvement in BP (11,45), amelioration of uremic tumoral calcinosis (46,47), decrease in thickness of coronary artery intima media (10), and reduction in left ventricular mass index (48). However, whether successful PTX can affect cardiac autonomic outflow in severe SHPT remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas shunting of blood to a low-resistance area (arteriovenous access), resulting in hypoperfusion distal to the anastomosis, has been suggested as the cause, increased resistance to blood flow offered by the presence of arterial stenosis also can play a critical role (5,8 -10). Furthermore, distal arteriopathy that commonly is seen in patients with vascular calcification and diabetes may be an important factor that leads to the development of DHIS (11,12).…”
Section: Pathophysiologymentioning
confidence: 99%
“…22 Elevated PTH levels and phosphorus concentration also lead to increased vascular calcification, which could explain the increase in PP values. 23 It is also possible that the association between raised PTH and phosphorus, and lower PP represents survival of those patients with the healthiest blood vessels for the longest period, while PTH and phosphorus concentration continue to rise in parallel with the duration of dialysis. 24 The impact of ultrafiltration and volume control on HD BP is a well-known fact.…”
Section: Discussionmentioning
confidence: 99%